1999
DOI: 10.1037/0096-3445.128.3.309
|View full text |Cite
|
Sign up to set email alerts
|

Working memory, short-term memory, and general fluid intelligence: A latent-variable approach.

Abstract: A study was conducted in which 133 participants performed 11 memory tasks (some thought to reflect working memory and some thought to reflect short-term memory), 2 tests of general fluid intelligence, and the Verbal and Quantitative Scholastic Aptitude Tests. Structural equation modeling suggested that short-term and working memories reflect separate but highly related constructs and that many of the tasks used in the literature as working memory tasks reflect a common construct. Working memory shows a strong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

203
2,481
22
43

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 2,554 publications
(2,749 citation statements)
references
References 78 publications
203
2,481
22
43
Order By: Relevance
“…We chose the complex span paradigm, which is a well-established measure of WM capacity (cf. Conway et al, 2005), as well as an excellent predictor for reasoning (e.g., Engle, Tuholski, Laughlin, & Conway, 1999;Süß, Oberauer, Wittmann, Wilhelm, & Schulze, 2002). Moreover, in our recent study mentioned above , we found that training with complex span tasks was more effective than training with other tasks of WM capacity in terms of transfer to untrained WM and reasoning tasks.…”
supporting
confidence: 51%
“…We chose the complex span paradigm, which is a well-established measure of WM capacity (cf. Conway et al, 2005), as well as an excellent predictor for reasoning (e.g., Engle, Tuholski, Laughlin, & Conway, 1999;Süß, Oberauer, Wittmann, Wilhelm, & Schulze, 2002). Moreover, in our recent study mentioned above , we found that training with complex span tasks was more effective than training with other tasks of WM capacity in terms of transfer to untrained WM and reasoning tasks.…”
supporting
confidence: 51%
“…The contents of working memory are often viewed as an activated subset of information from long-term memory, with the focus of attention determining what information becomes active (Cowan, 1988;Engle et al, 1999). Such a model does not require that the attentional controller, perhaps DLPFC, actually represents the information.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the vast storage in human long-term memory, WM has been demonstrated to have a capacity limited by the number of items [8,9] and this is strongly correlated with general cognitive ability [10,11] . Recent advances in studying visual WM have shown a precision limit of representations in WM besides the capacity limit [12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…However, with regard to WM the role of the delay activity in sensory cortices has been thought to differ from that of the PFC. The former has been thought to represent and store selective sensory information and the latter has been considered to exert attentional bias and cognitive control over the former (see reviews [6,7] ).Despite the vast storage in human long-term memory, WM has been demonstrated to have a capacity limited by the number of items [8,9] and this is strongly correlated with general cognitive ability [10,11] . Recent advances in studying visual WM have shown a precision limit of representations in WM besides the capacity limit [12][13][14][15][16] .…”
mentioning
confidence: 99%